2013
DOI: 10.3389/fnbeh.2013.00141
|View full text |Cite
|
Sign up to set email alerts
|

Urethane anesthesia depresses activities of thalamocortical neurons and alters its response to nociception in terms of dual firing modes

Abstract: Anesthetics are often used to characterize the activity of single neurons in vivo for their advantages such as reduction of noise level and convenience in noxious stimulations. Urethane has been a widely used anesthetic in thalamic studies under the assumption that sensory signals are still relayed to the thalamus under urethane anesthesia and that thalamic response would therefore reflect the response of the awake state. We tested this assumption by comparing thalamic activity in terms of tonic and burst firi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 19 publications
2
15
0
Order By: Relevance
“…The effects described here might have been modulated by urethane anesthesia that influences excitatory and inhibitory neuronal firing (Hara and Harris, 2002) and, consequently, might differ from multisensory interactions in the awake state (Iurilli et al, 2012; Ibrahim et al, 2016). Furthermore, it has been shown that urethane anesthesia strengthens thalamic burst firing which, in contrast to tonic firing mode, inhibits the transmission of sensory information to the cortex (Huh and Cho, 2013). By these means, the flow of unisensory and multisensory information to primary sensory cortex might be restricted under urethane anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…The effects described here might have been modulated by urethane anesthesia that influences excitatory and inhibitory neuronal firing (Hara and Harris, 2002) and, consequently, might differ from multisensory interactions in the awake state (Iurilli et al, 2012; Ibrahim et al, 2016). Furthermore, it has been shown that urethane anesthesia strengthens thalamic burst firing which, in contrast to tonic firing mode, inhibits the transmission of sensory information to the cortex (Huh and Cho, 2013). By these means, the flow of unisensory and multisensory information to primary sensory cortex might be restricted under urethane anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Urethane1.5 induced deeper anaesthesia than observed in the other groups, but yielded high ReHo, a seemingly contradictory finding that may be partly explained by the fact that urethane exerts modest effects on multiple receptor systems. However, one study in mice using the similar level of urethane reported depressed thalamic activity, indicating that there may also be other reasons for the retained ReHo under Urethane1.5 (Huh and Cho, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…CMG was conducted under urethane anesthetic, which preserves reflex voiding to continuous infusion with minimal impact on cystometric parameters . Urethane inhibits suprathalamic sensory transmission thereby suppressing cortical/social control over voiding, thus CMG under urethane anesthesia tests autonomic reflex bladder emptying in response to the physiologic challenge of continuous bladder filling …”
Section: Methodsmentioning
confidence: 99%